Impactful Islamic Education Strategy in Forming Future Cadres: Analysis of Youth Cadre Formation Patterns in Persis Sumedang - Agus Susilo Saefullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Da'wah education plays a strategic role in forming successor cadres who possess not only Islamic knowledge but also social competence and communal responsibility. Pemuda Persatuan Islam, as an autonomous cadre organization of Persatuan Islam (Persis), holds a significant position in preparing young generations to continue the mission of the jam’iyyah’s da'wah. This study aims to analyze the model of impactful da'wah education implemented by Pemuda Persis Sumedang through a cadre formation strategy that integrates ideological strengthening, pedagogical development, and collaborative social praxis. This research employs a descriptive qualitative method using interviews, observations, and documentation techniques. The findings reveal that da'wah education is conducted systematically and progressively through structured cadre stages (Ma’ruf and Tafiq I–III), leadership and organizational training, outreach programs in remote areas, disaster response engagement, industrial-based religious mentoring, and cross-organizational collaboration among Islamic youth movements. This model produces cadres who are not only capable of delivering religious messages verbally but also able to actualize da'wah through social service and community empowerment. Conceptually, this study contributes by formulating the construct of “impactful da'wah education” as an integrative cadre model that combines ideological, pedagogical, and measurable social action dimensions within a sustainable training system. Practically, the findings offer an applicable and replicable framework for Islamic youth organizations in responding to contemporary social challenges and digital transformation.